Shifting understandings of performance practice in an African context through auto-ethnography - Lejowa, Jessica Oreeditse (My University, 2010)
Abstract By critically analysing three pieces of devised performance, Even as I Walk (2008), They Were Silent (2009) and The Wages of Sin (2009), I argue that the concept of performance is not easily defined. Rather, it is an ever-changing phenomenon, which can become a useful platform for dialoguing about deeply personal and necessarily public and political subject matter. I locate myself and the theatre makers I worked with to create the three pieces, in the work by reflecting on and writing about the processes using auto-ethnography as a lens. The context within which I write, and within which my collaborators and I work, is that of our locations in very specific African, moral, cultural, political and creative impulses which we interrogate through the creative processes. Through the writing and reflecting, I arrive at various conclusions, including what I call ‘the methodology of not knowing,’ the importance of the group in facilitating the research and creative process, the necessity of redefining or renegotiation—for the purposes of both the research and the creative goals—our understandings of what performance is.
Keywords: performance; transgression; ritual; women; methodology